Barrier-to-Autointegration Factor 1 (BAF/BANF1) Promotes Association of the SETD1A Histone Methyltransferase with Herpes Simplex Virus Immediate-Early Gene Promoters - Hyung Suk Oh (American Society for Microbiology, 2015)
ABSTRACT We have shown previously that A-type lamins and intranuclear localization of the herpes simplex virus (HSV) genome are critical for the formation of the VP16 activator complex on HSV immediate-early (IE) gene promoters in murine cells, which implies a critical role for lamin A and its associated proteins in HSV gene expression. Because barrier-to-autointegration factor 1 (BAF/BANF1) has been thought to bridge chromosomes to the nuclear lamina, we hypothesized that BAF might mediate viral genome targeting to the nuclear lamina. We found that overexpression of BAF enhances HSV-1 replication and knockdown of BAF decreases HSV gene expression, delays the kinetics of viral early replication compartment formation, and reduces viral yield compared to those in control small interfering RNA-transfected cells. However, BAF depletion did not affect genome complex targeting to the nuclear periphery. Instead, we found that the levels of a histone-modifying enzyme, SETD1A methyltransferase, and histone H3 lysine 4 trimethylation were reduced on IE and early (E) gene promoters in BAF-depleted cells during HSV lytic infection. Our results demonstrate a novel function of BAF as an epigenetic regulator of HSV lytic infection. We hypothesize that BAF facilitates IE and E gene expression by recruiting the SETD1A methyltransferase to viral IE and E gene promoters. IMPORTANCE The nuclear lamina is composed of lamin proteins and numerous lamina-associated proteins. Previously, the chromatin structure of DNA localized proximally to the lamina was thought to be characterized by heterochromatin marks associated with silenced genes. However, recent studies indicate that both heterochromatin- and euchromatin-rich areas coexist on the lamina. This paradigm suggests that lamins and lamina-associated proteins dynamically regulate epigenetic modifications of specific genes in different locations. Our goal is to understand how the lamina and its associated proteins regulate the epigenetics of genes through the study of HSV infection of human cells. We have shown previously that A-type lamins are critical for HSV genome targeting to the nuclear lamina and epigenetic regulation in viral replication. In this study, we found that another lamina-associated protein, BAF, regulates HSV gene expression through an epigenetic mechanism, which provides basic insights into the nuclear lamina and its associated proteins’ roles in epigenetic regulation.